"We're not there to protect ourselves, we're there to talk about workforce planning": A qualitative study of policy dialogues as a mechanism to inform medical workforce planning. Issue 7 (July 2020) - Bruen, Carlos; Brugha, Ruairi
Highlights: We analyse policy dialogues as a formalised interactive mechanism for knowledge brokering. Policy dialogues can add value to both policy and research processes. Policy dialogues facilitate evidence-focused interaction between policy stakeholders beyond 'business-as-usual' relations. Policy dialogues strengthen the policy-relevance of research data collection, analysis, and dissemination. Contextual factors, e.g. competing policy priorities, limit dialogue impact on policy processes. Abstract: Introduction: To address a disjuncture between medical workforce research and policy activities in Ireland, a series of national level policy dialogues were held between policy stakeholders and researchers to promote the use of research evidence in medical workforce planning. This article reports on findings from a qualitative study of four policy dialogues (2013–2016), the aim of which was to analyse policy dialogues as a mechanism for knowledge-sharing and interaction to support medical workforce planning. Methods: Descriptive qualitative study design involving in-depth interviews with policy stakeholders and researchers (n = 13) who participated in the policy dialogues; thematic analysis of interview transcripts. Findings: Periodic policy dialogues, with discussion focused on research evidence, provided an enabling environment for exchange and interaction between policy stakeholders and researchers, and between policy stakeholders themselves. Findings foreground the significance of the policy-making context, in terms of how people interact during policy dialogues, and how research can potentially (or not) inform medical workforce planning. Conclusion: Policy dialogues provide a mechanism for improving knowledge exchange and interaction between policy stakeholders and researchers. Situated within the policy context, policy dialogues also add value to: a) policy-making processes by facilitating interactions between policy stakeholders outside the day-to-day business of formal and sometimes adversarial negotiation; b) research processes, including exposing researchers to the complexity of health workforce planning, and health policy more generally.